2018
DOI: 10.1080/13639080.2018.1459513
|View full text |Cite
|
Sign up to set email alerts
|

Cultural stereotypes and professional self-socialisation in the transition from education to work

Abstract: A key insight from studies of gender segregation is that the allocation of different groups to different positions in the labour market is strongly related to ascribed status. Shared gendered cultural beliefs generally portray men as more competent and of a higher status than women, and position some workers as more suited than others to perform different types of work and tasks. Yet, although much work has been done on status and gender segregation, this research tends to overlook the intersections of gender,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…It can be full-time, part-time or casual work. It helps to improve state of students' budgets and at the same time it allows to gain valuable experience [21,22,23].…”
Section: Resultsmentioning
confidence: 99%
“…It can be full-time, part-time or casual work. It helps to improve state of students' budgets and at the same time it allows to gain valuable experience [21,22,23].…”
Section: Resultsmentioning
confidence: 99%
“…They argue that identifying with what is seen as core competence in the profession is crucial to pursuing a career, to persistence and to the feeling of being suited to a profession. Previous research has demonstrated that an individual's perceived ability to meet the competence ideals in educational programmes strongly influences identification and a sense of belonging (Orupabo 2018). Making use of the concept of self-socialisation (Heinz 1999), Orupabo (2018) shows how students' sense of professional suitability is an ongoing learning process, influenced by the competence ideals in specific educational programmes.…”
Section: Previous Research and Theoretical Perspectivesmentioning
confidence: 99%
“…Furthermore, studies of what promotes gender inclusion and exclusion in education suggest that the gender minority lacks both professional and social confidence in heavily gender-typed educational fields and professions, and therefore is less likely to persist than the gender majority (Cech et al 2011;Stott 2007). However, being the underrepresented gender in an educational context does not automatically lead to marginalisation and exclusion, since different educational contexts might harbour different possibilities for gender inclusion and exclusion (Orupabo 2018). This calls for an attention to what promotes students' confidence in their ability to fulfil the knowledge, skills and personal qualities required in gendertyped study programmes.…”
mentioning
confidence: 99%
“…One student summarised in their response the voice of many when they stated The factors identified as benefits of completing a degree, particularly external motivators such as the ability to provide for one's family, reinforce a desire to keep at study and reach towards course completion, which are often shared by Pacific university students. The desire to also positively shape and create better opportunities beyond the margins, stereotypes and labels generally afforded within Western societies (Orupabo, 2018) where also at the core of such responses.…”
Section: Question 7: What Do You See As the Main Benefits Of Completimentioning
confidence: 99%